REDEPLOYING PARKER, POST-COLONIALLY - Macleod, Catriona; Wilbraham, Lindy (PINS-Psychology in Society, 2025)
In this paper we review two of Ian Parker’s recent books: Critical discursive psychology and Qualitative psychology: Introducing radical research. Although the books address different audiences (academics versus students) and talk to different problematics (theory versus research), taken together they represent useful resources for those wishing to take a critical stance with regards to the standard fare of psychology, to use critical theory in understanding social and psychological phenomena, and to engage in progressive research. As such, both theory and research methods appear as “tools”, and we suggest reading Parker sideways, shifting his intellectual trajectory into directions that illuminate colonial and post-colonial issues through empirical/textual application to real South African contexts. By way of illustration, we offer a post-colonial reading of Parker’s work on post-modernism. Concluding comments on tactics for a “post-colonial analysis of discourses” are offered.